Artistic practices in contemporary Asia - Abdullah, Sarena (Intellect, 2018)
In the past decades, the global geopolitical economy has shifted its focus from Europe to United States, and then in the new millennium, to Asia. Under the geographical premise of Asia, this issue focuses on the selection of papers that address the artistic practice that linked art to the broader shifts of political, social and public spheres. The contemporary artistic practices in Asia have long evolved and have grown exponentially since the 1990s, with the increasing regional biennials and triennials, the establishment of new contemporary art museums and the success of various Asian artists. This encouraged the establishment of various alternative artistic practices that reflected the everevolving and mutative artistic practices in contemporary Asia.